2016
DOI: 10.1111/apt.13813
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab provides clinical benefit over 1 year in patients with active inflammatory bowel disease - a prospective multicenter observational study

Abstract: Among patients who started vedolizumab for active inflammatory bowel disease, clinical remission rates are 21-25% after 54 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
4
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 34 publications
18
115
4
8
Order By: Relevance
“…Although controlled clinical trials suggested that vedolizumab might induce more rapid clinical remis sion in ulcerative colitis than in Crohn's disease 59,60 , sub sequent real world data confirmed efficacy of this drug for moderate-severe Crohn's disease in routine clinical practice 64 with similar rates of long term remission in Crohn's disease and ulcerative colitis 65 . The reasons for potential differences between vedolizumab in Crohn's disease versus ulcerative colitis remain to be deter mined.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Although controlled clinical trials suggested that vedolizumab might induce more rapid clinical remis sion in ulcerative colitis than in Crohn's disease 59,60 , sub sequent real world data confirmed efficacy of this drug for moderate-severe Crohn's disease in routine clinical practice 64 with similar rates of long term remission in Crohn's disease and ulcerative colitis 65 . The reasons for potential differences between vedolizumab in Crohn's disease versus ulcerative colitis remain to be deter mined.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Clinical response to vedolizumab at week 10 was observed in 46% of these patients. In a real-world scenario, vedolizumab was found effective to induce clinical remission at week 54 in 25% of patients [8]; a further study showed a slightly greater remission rate of 35% after a median follow-up of 39 weeks [18]. Both cohorts covered ≥90% of patients that were TNF antagonist experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Further therapeutic options were opened by the introduction of vedolizumab and ustekinumab, monoclonal antibodies against α4β7 integrin and interleukin 12/23p40. With respect to the TNF failure cohort of CD patients, retrospective data of real-world experience showed an initial clinical response to vedolizumab in about 60% and remission rates at week 54 between 21 and 25% [8]. A response to ustekinumab was demonstrated in 58% of patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…A German prospective study assessing the efficacy of vedolizumab induction therapy showed clinical remission at week 14 in 23.7% of the patients with Crohn's disease and 23.5% of the patients with ulcerative colitis [8]. In this patient group, clinical remission was achieved after 54 weeks in 21% of the patients with Crohn's disease and 25% of the patients with ulcerative colitis [9]. Recently, a French prospective study including 173 patients with Crohn's disease and 121 with ulcerative colitis found that up to one-third of the patients were in steroid-free clinical remission at week 54 of vedolizumab therapy, but a significant number of patients experienced a loss of response during the first year of treatment [10].…”
Section: Doi: 101159/000492322mentioning
confidence: 87%